Bald on Records Used by Aang The Main Character in Avatar: The Last Airbender 2024 - Alfarizi, Muhammad Zendi; Yasmin, Alica Nurmalinda; Fatiha, Nadhira Thauriq (PROJECT (Professional Journal of English Education), 2025)
The purposes of this research are to analyze types of Bald on Record strategies and to investigate factors that influence Aang in the film. The subject of the research is the series of Avatar: The Last Airbender 2024. The researchers used a descriptive qualitative method and the data were analyzed using the theory of Brown and Levinson. This series has 8 episodes. There is a total amount of 30 data obtained by the researchers in Bald on Records strategies and Influencing Factors types. The result for Bald on Records shows that there are 11 Great Urgency, 6 Metaphorical Emphasize, 4 Metaphorical High Valuation, 0 Channel Noise, 2 Task Oriented, 1 Speaker is Powerful, 3 Sympathetic Advice or Warning, 0 Permission That Hearer has Requested, 0 Welcoming, 1 Farewell, and 2 Offer. The types of Influencing Factors, there are 4 Payoffs, 6 Social Distance, 13 Relative Power, and 7 Absolute Rankings of Imposition. The conclusion is that Aang used Great Urgency in Bald on Records more often than others because he faced urgent situations frequently, he used Relative Power in Influencing Factors than others because he is more powerful than other characters.